2021
DOI: 10.1038/s41419-020-03364-2
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21-regulated Annexin A2 plasma membrane trafficking facilitates osteosarcoma cell differentiation through the TFEB-mediated autophagy

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor in children and adolescents, which is characterized by dysfunctional autophagy and poor differentiation. Our recent studies have suggested that the tripartite motif containing-21 (TRIM21) plays a crucial role in regulating OS cell senescence and proliferation via interactions with several proteins. Yet, its implication in autophagy and differentiation in OS is largely unknown. In the present study, we first showed that TRIM21 could promote OS ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Autophagy has been implicated in the differentiation of osteoblasts. It has been demonstrated that autophagy-related proteins are involved in osteoblast differentiation and bone formation, and other studies have reported that autophagy affects osteoblast mineralization and osteocyte network structure (39,40). Mouse models knocking out autophagy genes have shown a significant reduction in osteophagy volume, number, and thickness (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been implicated in the differentiation of osteoblasts. It has been demonstrated that autophagy-related proteins are involved in osteoblast differentiation and bone formation, and other studies have reported that autophagy affects osteoblast mineralization and osteocyte network structure (39,40). Mouse models knocking out autophagy genes have shown a significant reduction in osteophagy volume, number, and thickness (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…99 TRIM21 overexpression was shown to upregulate the main autophagic marker light chain 3-II, triggering the formation of autophagosomes and their subsequent delivery to lysosomes. 100 Autophagy plays an important role in renal function, mainly by maintaining podocyte homeostasis and viability, insulin sensing and permeability of the renal filtration barrier to albumin. 101 The downregulation of autophagy with accompanying histological renal lesions was observed in patients with diabetes with proteinuria.…”
Section: Trim21 Proteasome Initiation and Autophagosome-like Structuresmentioning
confidence: 99%
“…microtubule‐associated protein 1A/1B‐light chain 3] 99 . TRIM21 overexpression was shown to upregulate the main autophagic marker light chain 3‐II, triggering the formation of autophagosomes and their subsequent delivery to lysosomes 100 . Autophagy plays an important role in renal function, mainly by maintaining podocyte homeostasis and viability, insulin sensing and permeability of the renal filtration barrier to albumin 101 .…”
Section: Effects Of Fcγr Activation In Kidney Cellsmentioning
confidence: 99%
“…Annexin A2 (ANXA2), a 39-kDa phospholipid-binding protein, belongs to the Annexin family [ 18 ] and plays a key role in membrane organization, traffic, and fusion [ 19 , 20 ]. With the high involvement in dynamic events of membrane events [ 21 , 22 ], ANXA2 plays a crucial role in mediating autophagy [ 23 , 24 ]. Indeed, ANXA2 ablation leads to the defects of phagophore membrane initiation [ 25 ] and the deficiency in autophagy setting [ 26 ].…”
Section: Introductionmentioning
confidence: 99%